Motif Dalam Menonton YouTube Channel RANS Entertainment Pada Kalangan Dewasa Kota Denpasar - Meyra, Miranda Sanna; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium; Vol 4 No 1 (2023): Jurnal Ilmu Komunikasi Vol 4 No 1 Tahun 2023, 2023)
Abstract The Daily Vlog presented by RANS Entertainment has become a favorite program for RANS YouTube viewers that covers and tells the real life of the daily activities of the RANS family. The purpose of this research is to find out the motives for watching YouTube RANS Entertainment among adults in Denpasar City. Data in quantitative descriptive research using the positivist paradigm were collected through questionnaires and analyzed using descriptive statistical analysis techniques. Based on the uses and gratification theory and a combination of motives according to McQuail, Papacharissi and Rubin, this study found that the motive that most encouraged respondents to watch RANS Entertainment's YouTube Channel was the convenience motive and the lowest motive was integration and social identity and the cross tabulation results obtained, respondents those aged 39-45 years have a higher motive or drive in watching RANS Entertainment's YouTube Channel than the other two age categories. Keywords: Motives, YouTube Video, Vlog, RANS Entertainment, Adults.